Biology and political behavior - Peterson, Steven A.; Somit, Albert (Emerald, 2011)
This volume examines cutting edge research in the study of biology and politics. Following an introduction from the editors it is divided into two main sections. The first part of the book explores the linkage between evolution, genetics and politics with initial chapters on abandoned baby legislation, a model of action and norms, and the biopolitics of primates. The next four chapters have a special focus on the use of twin studies to study political phenomena and provide a biological critique of twin studies, phenotypic measurement issues and twin studies, a survey of twin studies research, and an example of using twin studies to explore politically relevant behaviour. The second section looks at the relationship of brain science to our understanding of politics. With respect to the applicability of brain science it features chapters summarizing what literature exists as well as how to use neuroimaging techniques to study political behaviour.
Keywords: Political Science -- General.; Political science & theory.; Sociology.; Biopolitics.; elektronické knihy; electronic books